Penemuan Pola Asosiasi pada Data Transaksi PT Bumi Kaya Kuliner Menggunakan Algoritma Apriori - Chendana, Nicholas Ignatius; Mardiani, Mardiani (Universitas Multi Data Palembang, 2025)
PT Bumi Kaya Kuliner is a company operating in the culinary sector which every day stores a lot of transaction data in Excel format containing sales of food and beverage products. The company wants to utilize the stored transaction data to provide future strategy suggestions. So data mining analysis can be carried out using an a priori algorithm using the CRISP-DM method. The results obtained from this research are in the form of menu combinations that are often ordered simultaneously and the output of this research is also in the form of a dashboard application which is implemented using Visual Studio code and the Python programming language with the aim of being able to be used by companies to see calculation results directly.